34‐2: Invited Paper: Novel Four‐Transistor Pixel Circuit Using Source‐Follower Structure for Field‐Sequential‐Color Blue‐Phase Liquid Crystal Displays. Issue 1 (2nd June 2017) - Hung, Chia-Che; Hsieh, Hsiang-Yuan; Lin, Ya-Ting; Yu, Fang-Cheng; Tsao, Tzu-I; Lu, Min-Yao; Tseng, Bo-Shiang; Hung, Ching-Lang; Huang, Pu-Jung; Chen, Yi-Ting; Hsieh, Chia-Ting; Lin, Ching-Hsiang; et al.
Abstract : We propose a novel pixel circuit using source‐follower structure to be independent of frequency effect of blue‐phase liquid crystal displays (BPLCDs). Simulation results indicated that required gray‐level‐voltages across the BPLC could be achieved accurately when a proper threshold voltage of the driving TFT was chosen. We also successfully fabricated a 12.7‐inch prototype BPLCD using the proposed pixel circuit driven with a field‐sequential‐color method of 240 Hz.